Performance of Broiler Chickens on Commercial Diets Mixed with Whole or Ground Wheat of Different Varieties - Yasar, Sulhattin (International Journal of Poultry Science, 2002)
To study the effects of mixing commercial diets with whole wheat on           bird performance with respect to growing ages, each of four whole or           ground wheat varieties was mixed with commercial diets at the presence           or absence of enzyme at the following rates: 10% from 7 to 14 d of age,           20% from 14 to 21 d of age, 30% from 21 to 28 d of age, and 50% from           28 to 35 d of age. A control group of broiler chickens was fed only           with commercial diets throughout. Birds performed well with the diets           mixed with 10 and 20% wheat whether ground or whole. Feed intake of           birds significantly (P